(untitled) (Bangladesh Journal of Botany, 2019)
Uptake and translocation of radiocesium artificially added to sand soil cultivated with barley as affected by different rates of potassium were traced in outdoor pot experiment. Experimental soil was contaminated with 0.01 and 0.1 mM 137Cs equal to (200 and 400 Bq/kg) in the form of CsCl and incubated for 14 days prior to 150 days plant growth period. The transfer factor (TF) average values from soil-to-total biomass were found to range from 0.40 up to 0.53 as affected by interaction between tested treatments. Increasing K rates from 125 to 250 kg/ha markedly reduced the mean averages of TFs of 137Cs from soil-to-roots by about 24 to 68%, respectively and from soil-to-total biomass by about 36 and 74%, respectively lower than corresponding control. In all cases, the discrimination factor was below unity, indicating that Cs is less efficiently absorbed from soil than its nutrient analogue K.